1998
DOI: 10.1038/sj.onc.1201865
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for transformation induced by the Axl receptor tyrosine kinase

Abstract: The Axl receptor tyrosine kinase is a transforming oncogene in NIH3T3 cells. In order to de®ne structural requirements of the Axl receptor necessary for transformation we passaged recombinant retroviruses carrying the axl cDNA in NIH3T3 cells, generating randomly mutated axl variants. Using this strategy, we have isolated three axl viral strains (1B1, SV8, and FFa4) that show augmented 3T3 cell transforming capacity associated with elevated p140 Axl . Upon sequencing, the 1B1 and SV8 proviruses possessed only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 32 publications
3
36
0
Order By: Relevance
“…Various studies have demonstrated roles of GAS6/AXL in regulating cell growth and survival in normal and cancer cells (Stitt et al, 1995;Wimmel et al, 2001). AXL is characterized by a unique extracellular composition consisting of immunoglobulin-like and fibronectin-type III-like domains, which are also found in adhesion molecules of the cadherin and immunoglobulin superfamily, therefore suggesting that AXL might regulate cell adhesion (Burchert et al, 1998). Other evidence is consistent with roles of AXL in tumor cell invasion, metastasis and survival (Jacob et al, 1999;Holland et al, 2005;Mahadevan et al, 2007).…”
Section: Introductionmentioning
confidence: 70%
“…Various studies have demonstrated roles of GAS6/AXL in regulating cell growth and survival in normal and cancer cells (Stitt et al, 1995;Wimmel et al, 2001). AXL is characterized by a unique extracellular composition consisting of immunoglobulin-like and fibronectin-type III-like domains, which are also found in adhesion molecules of the cadherin and immunoglobulin superfamily, therefore suggesting that AXL might regulate cell adhesion (Burchert et al, 1998). Other evidence is consistent with roles of AXL in tumor cell invasion, metastasis and survival (Jacob et al, 1999;Holland et al, 2005;Mahadevan et al, 2007).…”
Section: Introductionmentioning
confidence: 70%
“…In the present study, we confirm that overexpression of MZF1 is tumorigenic, and for the first time, we report that MZF1 induces tumor growth and metastasis through the transactivation of Axl, thus adding to the molecular targets and mechanisms that can mediate an oncogenic potential of MZF1 in epithelialderived tissues. Axl has been reported as a transforming gene (21) that is overexpressed in several tumors (22)(23)(24)(25)(26)(27), and the Gas6/Axl signaling pathway is known to induce cell proliferation, antiapoptosis, migration, invasion, and angiogenic processes, which are most likely mediated through Ras, Src, mitogen-activated protein kinase/extracellular signal-regulated kinase, phosphoinositide 3-kinase/Akt, and NF-κB signaling pathways (14,15,19,29,31,32,(44)(45)(46)(47)(48)(49). However, still further studies are needed to enhance the understanding of the downstream components of the Gas6/Axl signaling axis in tumor formation.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular signaling of Axl is also activated by its homophilic and heterophilic interactions (19), mediated mainly by a multisubstrate docking site (20). Overexpression of Axl can transform fibroblasts even in the absence of a ligand (21), this is at least in part being mediated by Gas6/Axl-induced activation of mitogen-activated protein kinase/extracellular signal-regulated kinase and phosphoinositide 3-kinase signaling. Following its identification in myeloid leukemia, Axl overexpression has been reported in several types of human solid cancers (22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Axl can transform fibroblasts even in the absence of a ligand (Burchert et al, 1998). Axl is known to induce cell survival (Melaragno et al, 2004;van Ginkel et al, 2004), proliferation (Stenhoff et al, 2004;Sainaghi et al, 2005), stimulation of cell migration and cell-cell adhesion (McCloskey et al, 1997).…”
Section: Introductionmentioning
confidence: 99%